Investor protection strategies in crowdfunding regulation : The 4-I's model - Salo-Lahti, Marika; Annola, Vesa (Routledge, 2022)
Crowdfunding is an alternative form of financing, which is typically operated by online platforms. The regulation on crowdfunding has been very heterogeneous with different national legislations. Despite the differences, one central goal of the financial market regulation is typically to protect investors. This chapter focuses on investor protection strategies in crowdfunding regulation. In order to tackle and systematize the strategies, we build and present a “4-I's model”. The model consists of Investor, Investment, Intermediary, and Information parts. In our analysis of the model, we concentrate mainly on the new European Union (EU) regulation on crowdfunding, which can effectively boost the growth of the crowdfunding sector in the EU.
Keywords: Crowdfunding regulation; systematization; regulation strategies; investor protection; fi=Talousoikeus|en=Business Law|